Therapeutic Effects of Cordia myxa-Derived Zinc Oxide Nanocomposite on the Doxorubicin-Induced Hepatosplenic Histopathology in a Murine Model: Protective Effect of Cordia myxa Nano-Extract on DOX-Treated Mice - Reem Abdul Raheem Mirdan Alsaad; Batool A. Hussien; Rashid, Ahmed (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Doxorubicin (DOX), a strong antineoplastic agent, has been linked to remarkable dose-limiting hepatotoxicity and splenic injury. Cordia myxa, a medicinal plant, has been investigated for its organ-protective and antioxidant properties and offers potential as a potential antidote. Nanoparticle-mediated delivery may improve therapeutic efficacy. This research aimed to determine the therapeutic capability of a zinc oxide-derived nano formulation of Cordia myxa extract against liver and spleen damage in albino mice caused by the DOX-induced histopathology Methods: The six cohorts (n=8) comprised 48 male albino mice. Distilled water was administered to the control group. The experimental groups were administered either the nano-extract (5 or 10 mg/kg), DOX (0.12 mg/kg), or a mixture of these for a duration of 30 days. The splenic and hepatic tissues were subjected to histopathological analysis after the treatment through the Eosin (H&E) and Hematoxylin staining. Results: The group subjected to only DOX demonstrated significant hepatic architectural derangement, including binucleation and hepatocyte atrophy, as well as distinct splenic congestion and red pulp expansion. In contrast, subjects administered nano-extract demonstrated normal tissue histology. Simultaneous nano-extract administration, especially at a 10 mg/kg dose, markedly reduced these pathological alterations, preserving near-normal hepatic integrity and diminishing splenic changes. Conclusion: The nano formulation of Cordia myxa offers significant defense against DOX-induced histopathological injuries in the spleen and liver. The results indicate its potential use, as it can aid in improving the organ toxicity that has been linked to chemotherapy.